Oppressive Staff Dynamics at an Intentionally Diverse Urban Charter School. Issue 3 (3rd May 2020) - Singer, Jeremy
Abstract: City Preparatory Academy (CPA) is a charter school in a midwestern city that intentionally serves a racially and socioeconomically diverse student population. This exploratory research began as an attempt to document growing concerns and disaffection shared by four staff members at CPA. These four women increasingly convened to discuss workplace hostility and issues of justice and equity, hoping to challenge some of the school's policies and practices. As they sought to promote changes, they faced oppressive dynamics that they attributed to the perspectives, dispositions, and practices of school leadership. This paper describes how particular institutional logics and interpersonal dynamics—shaped by neoliberalism, managerialism, class, and race—gave rise to a kind of non-generative politics that obstructed their efforts and ultimately disaffected them from the school. While the study is primarily an exploration of the context of this particular school, it highlights the need for a critical institutional perspective that situates schools within their sociopolitical context and connects organizational structures, routines, and culture with the beliefs and behaviors of school leaders.